2014
DOI: 10.1002/cplu.201400028
|View full text |Cite
|
Sign up to set email alerts
|

In Situ Growth of Noble‐Metal Nanoparticles on Cu2O Nanocubes for Surface‐Enhanced Raman Scattering Detection

Abstract: Gold and silver nanoparticles with a narrow size distribution were grown in situ on the surfaces of Cu2O nanocubes through a wet‐chemical reduction route. The Cu2O nanocubes serve as both the substrate and reducing agent. The as‐prepared Cu2OAu and Cu2OAg nanocomposites still retain the cubic morphology of the original Cu2O nanocubes. The Cu2OAu and Cu2OAg nanocomposites can serve as effective surface‐enhanced Raman scattering (SERS) substrates. Rhodamine 6G as a Raman probe was applied to determine the ef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(7 citation statements)
references
References 46 publications
0
7
0
Order By: Relevance
“…Besides the intrinsic nature of separation of charge between the two facets, the synergetic effect of those catalysts also played a significant role in enhancing photocatalytic performances. So far, lots of Cu 2 O‐based heterogeneous structures have been reported, and the synthetic routes mainly focused on light‐induced deposition or galvanic deposition . In this section, we plan to discuss the site‐selective deposition of noble NPs on the preferential faces, edges, or corners of Cu 2 O crystals.…”
Section: Facet‐controlled Depositionmentioning
confidence: 99%
See 1 more Smart Citation
“…Besides the intrinsic nature of separation of charge between the two facets, the synergetic effect of those catalysts also played a significant role in enhancing photocatalytic performances. So far, lots of Cu 2 O‐based heterogeneous structures have been reported, and the synthetic routes mainly focused on light‐induced deposition or galvanic deposition . In this section, we plan to discuss the site‐selective deposition of noble NPs on the preferential faces, edges, or corners of Cu 2 O crystals.…”
Section: Facet‐controlled Depositionmentioning
confidence: 99%
“…In this context, the inexpensive, non‐toxic and abundantly available Cu 2 O nanomaterials, with unique optical and electrical properties, have recently aroused general attention, due to their outstanding morphology‐dependent applications in catalysis (gas oxidation, CO 2 reduction, organocatalysis, electrocatalysis, and photocatalysis, sensing (gas sensors, ion detection, and surface‐enhanced Raman scattering (SERS), as adsorbents, biotoxicity, as chemical templates and energy‐related processes (water splitting, solar energy conversion and lithium‐ion batteries. Compared to Cu 2 O nanowires or nanorods, nanospheres, hollow structures, self‐assembled superstructures, and Cu 2 O polyhedra enclosed by high‐index planes, the preparatio...…”
Section: Introductionmentioning
confidence: 99%
“…However, the nanoparticles of these metals would form on Cu 2 O (described by the SEM images of typical samples in Figure S2 of the Supporting Information) under the controlled metal loading level similar to the current preparation of Rh–Cu 2 O samples. Such an M–Cu 2 O interface with metal nanoparticles anchored has been intensively studied in literature works. In view of metal dispersion of these samples, most metal atoms would be sealed inside metal particles, thus leading to a poor contact of the metal with Cu 2 O. Unlike them, the absence of Rh electronic diffractions and the slight deviation of Cu 2 O electronic diffraction on current Rh–Cu 2 O catalysts suggested that Rh would be highly dispersed on the surface of the Cu 2 O substrate through the redox etching–replacing reaction process.…”
Section: Resultsmentioning
confidence: 99%
“…For instance, it has been shown that thermal energy (either from Raman measurement or probe temperature) degrades the SERS substrates over time resulting in low sensitivity toward analyte molecules . Nanocomposites with metal oxides and noble metal particles show very large SERS intensity, for instance nanocomposites of metal oxides including CuO, Cu 2 O, ZnO, and TiO 2 with Au or Ag nanoparticles, with improved stability compared to single noble metals owing to a synergistic effect of noble metal component and the metal oxide support resulting from a charge transfer process between the noble metal and adsorbed molecules and at the interface between the noble metal and the metal oxide nanostructures. In general, EM enhancement is solely responsible for the SERS enhancement.…”
Section: Nanomaterials For Sensingmentioning
confidence: 99%